Anti-inflammatory Activity of Constituents Isolated from Aerial Part ofAngelica acutilobaKitagawa - Nguyen, Huu Tung (Wiley, 2016)
Recently, the resources of medicinal plants have been exhausting. The root ofAngelica acutilobais one of the most important ingredients in Japanese Kampo medicine for the treatment of gynecological diseases. In our search for alternative medicinal plant resources of the root ofA. acutiloba, we found that its aerial part has the anti-inflammatory potency as well as the root. Phytochemical investigation of the aerial part resulted in the isolation of four compounds including a new dimeric phthalide, namely tokiaerialide (2), along with Z-ligustilide (1), falcarindiol (3), and bergaptol (4). Next, we investigated thein vitro anti-inflammatory activity of 1–4 in lipopolysaccharide-stimulated RAW264 macrophages. Among the isolated compounds, 1 exhibited the most potent inhibition against lipopolysaccharide-induced production of prostaglandin E2,nitricoxide,and pro-inflammatory cytokines (interleukin-6 and tumor necrosis factor-α). Compounds 3 and 4 also inhibited all inflammatory mediators, but their inhibitory abilities were weaker than those of 1. Furthermore, 1, 3, and 4 strongly also induced heme oxygenase-1. These results suggest that 1, 3, and 4 potentially exert anti-inflammatory activity, and the aerial part ofA. acutilobamay be considered to be a useful medicinal resource for inflammatory diseases.